Hubungan Konsep Diri Dengan Kemampuan Mengenal Lambang Bilangan Anak Usia 5-6 Tahun Di Tk Negeri Pembina 1 Kota Pekanbaru - Eka Nurjanah; Yeni Solfiah; Nurlita Nurlita (Departement of Mathematics Education, 2024)
Early childhood is a group of children who are in a unique growth and development process. The ability to recognize numbers is part of mathematics which can develop children's cognitive abilities. The ability to recognize numbers in children is very important to develop, because it can be used in children's daily lives. Through the ability to recognize number symbols, it is hoped that it can improve children's cognitive abilities from an early age so that they develop strong mathematical foundations. The aim of this research is to determine the self-concept and abilities of children aged 5-6 years in Kindergarten Pembina 1 Pekanbaru City. correlational research with quantitative methods which aims to investigate the extent to which variation in one variable is related to variation and the population in this study was 140 children aged 5-6 years in Kindergarten Pembina 1 Pekanbaru City and used problem solving samples. The results of the research show that self-concept has an influence of 33.8% on children's ability to recognize number symbols. This situation provides information that there is a positive and significant relationship between self-concept and the ability to recognize number symbols. So it can be concluded that the relationship between self-concept and the ability to recognize number symbols in children aged 5-6 years at Kindergarten Negeri Pembina 1 Pekanbaru City is in the Good category, seen from the ability of children who can assess themselves according to their physical condition, can calculate the sequence of numbers from 1-10.